Pemanfaatan Media Pembelajaran Kahoot dalam Meningkatkan Motivasi Belajar Siswa - Iwan Usma Wardani; Rifaatul Mahmudah; Yanuarius Bria Seran; I Putu Suardipa (Lembaga Pengembangan Kinerja Dosen, 2025)
This mentoring aims to improve the learning motivation of students at SDN 4 Pancor through mentoring the use of technology-based interactive learning media, namely Kahoot. The study used four stages of implementation: planning, preparation, implementation, and evaluation. In the planning stage, initial observations and preparation of materials were carried out. The preparation stage involved checking the devices and internet used to access Kahoot. In the implementation stage, students were introduced to the Kahoot application, involved in interactive learning, and took tests through the platform. The results of the activity showed that the effective use of Kahoot was able to increase students' motivation and enthusiasm in learning, making the classroom atmosphere more interactive and enjoyable. Students became more active in participating and motivated to learn, thanks to the game elements presented by Kahoot. The conclusion of this study is that Kahoot can be used as an effective learning media in increasing students' learning motivation in the digital era